2018
DOI: 10.29312/remexca.v0i5.1292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación física y química de tezontle y su uso en la producción de tulipán

Abstract: Se evaluaron las características físicas y químicas del tezontle de dos granulometrías (3 y 5 mm) y su uso en la producción de tulipán (Tulipa gesneriana) cv. Ille de France, tomando como referencia el sustrato comercial ProMix®. El espacio poroso total (67 y 67.9%), el agua fácilmente disponible (2.9 y 2.3%) y la de reserva (1.9 y 1.1%) en el tezontle (3 y 5 mm, respectivamente) resultaron inadecuados para el cultivo de tulipán. El pH fue alcalino en tezontle y ácido en ProMix®; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Rodriguez Diaz et al [18] reported that the volcanic rock from the site from which the rock used in this investigation was obtained has a total porosity of 55.5% and an aeration porosity of 40.7%. Total porosity reported in other studies range from 67 to 74.7%, with aeration porosity levels of 39.2 to 44.4%, and a real density of 2.45 g cm −3 [19,20]. The packing depth was 2.80 m. The average temperature of the influent was 20.84 °C and the pH level was in the range 7.72 to 8.53, with an average of 8.17.…”
Section: Methodsmentioning
confidence: 95%
“…Rodriguez Diaz et al [18] reported that the volcanic rock from the site from which the rock used in this investigation was obtained has a total porosity of 55.5% and an aeration porosity of 40.7%. Total porosity reported in other studies range from 67 to 74.7%, with aeration porosity levels of 39.2 to 44.4%, and a real density of 2.45 g cm −3 [19,20]. The packing depth was 2.80 m. The average temperature of the influent was 20.84 °C and the pH level was in the range 7.72 to 8.53, with an average of 8.17.…”
Section: Methodsmentioning
confidence: 95%
“…However, other authors who have used red volcanic rock from the same area reported a total porosity of 55.5% and aeration porosity of 40.7% [ 28 ]. Total porosity reported in other studies ranges from 67% to 74.7%, with aeration porosity levels of 39.2–44.4% and real density of 2.45 g·cm −3 [ 29 , 30 ]. Other studies have reported an average pore diameter of 26.24 nm and apparent porosity/void space of 56.2% [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…El trasplante se realizó a los 30 días después de la siembra (dds) y consistió en colocar una plántula en bolsas de polietileno negro, llenadas con tezontle como sustrato; cuyas propiedades físicas fueron granulometría menor de 5 mm, 8.0% agua difícilmente disponible, 1.1% agua retenida, 2.3% agua fácilmente disponible, 56.5% capacidad de aireación, 67.9% espacio poroso total y 32.1% material sólido (Trejo-Téllez et al, 2013). Las bolsas con plántulas se establecieron en un diseño completamente al azar con 12 tratamientos y cuatro repeticiones, la unidad experimental la constituyeron 10 macetas, teniendo un total de 480 unidades experimentales, en un invernadero tipo túnel, con cubierta de polietileno UVII-720 y estructura de acero galvanizado, con ventilación lateral, localizado en el Colegio de Postgraduados, Campus Montecillo, estado de México.…”
Section: Trasplanteunclassified